MULTIDRUG RESISTANT BACTERIA IN DUMPSITE SOILS WITHIN ABRAKA, DELTA STATE, NIGERIA - Odum, Edward Ikenna; Idise, Okiemute E.; Ogogo, Dorris I. (FUDMA JOURNAL OF SCIENCES, 2020)
This study investigated the prevalence of antibiotic resistant bacteria in soils obtained from dumpsites in Abraka, Delta State. Four (4) dumpsites were assayed and composite soil samples were collected from each dumpsite. Isolates were obtained using the standard pour-plate method and pure cultures identified based on their cultural and biochemical characteristics. These were then subjected to antibiotic susceptibility test using the agar-disc diffusion method. A total of 61 isolates were obtained and identified to belong to nine (9) different genera. The isolates were Escherichia sp, Klebsiella spp, Staphylococcus sp, Bacillus spp, Pseudomonas sp, Proteus spp, Micrococcus sp, Streptococcus sp and Neisseria sp. Among the isolates obtained, Escherichia sp had the highest occurrence (26.23%) and Neisseria sp the lowest occurrence frequency of 1.63%. Pefloxacin was the least effective antibiotic as 96% and 76.67% of gram-positive and gram-negative organisms respectively, were resistant to the drug. All the isolates exhibited multidrug tolerance and a multiple antibiotic resistance (MAR) index of 0.8 was recorded for 31.15% of the isolates tested. The implication of these findings is a possible spread of persistent bacterial infections among the resident population. Proper waste management and siting of dumpsites in locations distant from residential areas will help in preventing the public health hazards associated with dumpsites.